Physico-chemical characterization of a lectin from pisum sativum “arveja” seeds and antifungical effect on fusarium oxysporum - Alberto Cáceres Huambo (2019)
By following previous method proceedings, a lectin was purified and characterized from Pisum sativum L. (Pea, Papilionaceae, Leguminosae) seeds through combination of one Sephadex G-75 gel filtration chromatography and a reverse phase HPLC in -Bondapack C18 column. The analysis in bidimentional electrophoresis (2D) showed a protein spot of 14 KDa and an isoelectrical point of 7.5. The molecular weight of 14 kDa was confirmed by mass spectrometry MALDI -TOF in 14 662.0 Da. The aminoacid composition showed an hydrophobical protein with basic features and bioinformatic analysis of the N-terminal sequence showed homology with other vegetable lectins. Likewise, most outstanding physical-chemical characteristics were: the glicoprotein nature and its specificity by D- mannose and D- glucose,the Ca2+ dependence and Mn2+ in order to show hemnogglutinan activity. The study of the fungicidal activity of V-2 fraction with the hemoglutinan activity over the Fusarium oxysporum reveals that lectin V-2 delays development of the fungi and inhibits its growing.